Migraine without aura in academics of physical therapy course - Guimarães, Élcio Alves; Rodrigues, Bárbara Martins; Makhoul, Kelly Duarte Lima; Sousa, Lucas Resende; Junior, Paulo Cézar Simamoto; Sousa, Gilmar da Cunha; Neto, Alfredo Júlio Fernandes (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Migraine is a primary headache that is usually severe. It is classified into five main categories, the two most important being migraine without aura and migraine with aura. The common, without aura, is characterized by periodic headaches that are usually pulsatile and unilateral, exacerbated by activities and associated with nausea, photophobia and phonophobia. In academics, headaches lead to loss of days of study and worse academic performance. Objective: The objective of this study was to evaluate the prevalence of migraine without aura in academics of the Physiotherapy course. Methodology: A total of 217 physiotherapy students over 18 years of age were evaluated, and the headache questionnaire was applied according to the International Classification of Headache Disorders, 3rd edition, 2014. Conclusion: It is concluded that there was prevalence of migraine without aura in academics of the Physiotherapy course.